Addressing change in physiotherapy education in South Africa - Seyi L. Amosun; Soraya Maart; Niri Naidoo (South African Journal of Physiotherapy, 2018)
Background: Recent demands for the decolonisation of curriculum in South Africa present challenges to students, academics and other stakeholders. This resulted in tensions in tertiary institutions, cumulating in student-led protests. The authors hypothesised that the lack of shared understanding of what this unexplored process may entail contributed to the dilemma.